2018
DOI: 10.1002/jcp.26857
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miRNA‐1 and miRNA‐133 in the proliferation and differentiation of myoblasts in duck skeletal muscle

Abstract: MicroRNA (miRNA)-1 and miRNA-133 are derived from the same bicistronic pairs with roles in skeletal muscle development. Many investigations have focused on the role of miRNA-1 and miRNA-133 in the regulation of skeletal muscle development in mammals and fish. However, the mechanisms of miRNA-1 and miRNA-133 underlying the differences in skeletal muscle development between different breeds are not well known.Our study found that the weights of body and breast at 42 days of age were greater in Cherry Valley duck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…The difference among these breeds might explain this phenomenon. Many miRNAs, such as let‐7, miR‐1, miR‐23a and miR‐24, have been demonstrated that had different functions during myogenesis in different animals (Allen & Loh, ; Chen et al, ; Drummond et al, ; Elia et al, ; Wada et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The difference among these breeds might explain this phenomenon. Many miRNAs, such as let‐7, miR‐1, miR‐23a and miR‐24, have been demonstrated that had different functions during myogenesis in different animals (Allen & Loh, ; Chen et al, ; Drummond et al, ; Elia et al, ; Wada et al, ; Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine follicular granulosa cells (pGCs) are important in follicles, and apoptosis of pGCs is the main cause of follicular atresia. In cells, miRNAs regulate a variety of important physiological and pathological processes, including cell proliferation (Han, Yin, & Zhang, ), differentiation (Wu et al, ), apoptosis (Yao, Pan, Du, Zhang, & Li, ), and hormone biosynthesis and secretion (Song et al, ). Previous studies have indicated that miR‐222 is an important regulatory factor for cancer development (Galardi et al, ; Gong et al, ; Gu et al, ; Guo et al, ; Huang, Ouyang, Wei, & Yu, ; Iida et al, ; le Sage et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-1 and miR-133 are specifically expressed in heart and skeletal muscle in humans, mice, and zebrafish (Wu et al, 2019). The miR-133 family contains three subfamilies: miR-133a-1, miR-133a-2 and miR-133b.…”
Section: The Roles Of Mir-1 and Mir-133 In Cardiovascular Related Dismentioning
confidence: 99%
“…During the metamorphosis of flatfish, the expression of HDAC4 decreased, which reduced its inhibition of MEF2 family transcription factors and promoted cell differentiation (Zhang et al, 2015). During the development of human fetus, the expression levels of miR-133 and miR-1 are directly proportional to the ability of myoblasts to form myotubes (Wu et al, 2019). MiR-133 and miR-1 upregulate the expression of MEF2 by specifically inhibiting HDAC4 and MEF2 then promotes cardiomyocyte differentiation with myogenic determination factor (MyoD).…”
Section: Myocardial Differentiationmentioning
confidence: 99%